Merit and Demerit of Generative Text AI for Indonesian Teachers’ Administration Load: Primary Teachers’ Perspective - David Ginola; Adhitya Amarulloh (Universitas Negeri Surabaya, 2025)
In the Indonesian educational system, teachers function as both educators and administrators; managing a large number of occupational processes critical for the functioning of the school, as well as meeting policy compliance mandates. This situation is particularly pronounced in public and rural schools which tend to be understaffed and under resourced. This leads to heightened levels of teacher stress, burnout, and poor quality of education. The recent emergence of generative text Artificial Intelligence (AI) provides new opportunities for alleviating the administrative burdens of teachers. Modern AI writing tools can perform report writing, lesson outline creation, and data entry due to their ability to human-equivalent compose. Such tools are likely to increase teachers’ productivity, reduce burnout, and improve the amount of time geared towards teaching interacting with students rather than monotonous work. Furthermore, the ability of AI to personalize instruction to vernaculars and the local curriculum strengthens its case for the diverse educational context of Indonesia. Research reveals that trust issues with AI content generators, cultural relevance of the material, concerns regarding data privacy, security, inequitable digital competences among staff members, as well as infrastructural gaps create formidable challenges towards effective AI integration. Additionally, the challenge concerning the potential impact of excessive dependence on AI systems on the professional evaluative skills of teachers also needs attention. This study provides an Indonesian perspective to inform diverse stakeholders policymakers, educators, and technology designers regarding the literature and case studies examining the advantages and disadvantages of generative text AI on the administrative burden of Indonesian teachers. The study advocates for the use of AI technologies that are secure, culturally relevant, inclusive, as well as sensitive and accessible to empower teachers for improved functionality beyond mere administration, to enhance the quality of education in Indonesia.